Estudo da circulação hidrodinâmica e da dispersão de óleo na zona costeira entre Macau e Galinhos RN - Gois, Daniel Melo Martins de (2008)
This paper presents a study on coastal hydrodynamics and the spread of an oil spill in waters off Macau and Galinhos, on the east coast of the state of Rio Grande do Norte in Northeast Brazil. This area has a very marked coastal dynamic owing to the complexity of its geomorphological features, developed in a regime of semidiurnal mesotides involving reefs, spits, estuaries, mangroves, lakes and dunes. The region also plays an important role in the socioeconomic development of the state, given that the production of oil, natural gas, salt and shrimp is concentrated there. The series of oil platforms is interconnected by a pipeline system that carries oil to the local terminal. This pipeline could leak at any moment, causing immense ecological damage. To gauge the risks of an oil leak and resulting contamination of the coastal region, two hydrodynamic scenarios were simulated. The results obtained were used to implement a contaminant transport model with the creation of various oil leak scenarios modeled at different volumes (from small to large) and intensities (sporadic and continuous), at points considered critical for the model (on two platforms and at two pipeline intersections), under different wind (summer and winter) and tidal (high and low at new, full and quarter moon phases) conditions. The use of hydrodynamic circulation computer models as a tool for representing a real project design has been increasingly frequent in recent years, given that they enable the realistic simulation of the hydrodynamic circulation pattern in bodies of water and an analysis of the impacts caused by contaminants released into the water. This study used the computer models contained in SisBAHIA®, in continuous development in the area of Coastal Engineering and Oceanography at COPPE/UFRJ